USM TO EXPAND EXPERT SERVICE IN AUDIOLOGY AND SPEECH - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, KUBANG KERIAN, 4 December 2016 " The Audiology and Speech Clinic provides an essential service that complements other available services, especially for Hospital Universiti Sains Malaysia (HUSM) which has high expertise in various fields," said the Director of the USM Health Campus, Professor Dr. Ahmad Sukari Halim when he launched the facility recently.